ประวัติศาสตร์กุลา - ตันเลิศ สุธิดา; ธานี พัชรี (วารสารศิลปศาสตร์ มหาวิทยาลัยอุบลราชธานี, 2016)
บทความนี้เป็นส่วนหนึ่งของโครงการทำนุบำรุงศิลปวัฒนธรรม เรื่อง การรวบรวมข้อมูลกลุ่มชาติพันธุ์กุลาในจังหวัดอุบลราชธานีและจังหวัดยโสธร เนื้อหาโดยรวมเน้นการนำเสนอพัฒนาการทางประวัติศาสตร์ เริ่มด้วยภูมิหลังและ ที่มาของกลุ่มชาติพันธุ์กุลา สาเหตุการเข้ามาตั้งรกรากในพื้นที่ศึกษา การปรับตัว ของกลุ่มชาติพันธุ์กุลาในจังหวัดอุบลราชธานี และผลกระทบจากการตั้งถิ่นฐาน ของกุลาในพื้นที่ศึกษาและวิจัย มุมมองที่ใช้ในการศึกษาคือประวัติศาสตร์ เริ่ม จากการรวบรวมข้อมูลเอกสาร การอ่านและวิเคราะห์เอกสาร การเก็บข้อมูล ภาคสนามเน้นการเก็บข้อมูลประวัติศาสตร์บอกเล่า การสังเคราะห์งานเอกสาร และข้อมูลภาคสนาม ผลการศึกษาพบว่า กุหล่า ในภาษาลาวหมายถึงกลุ่มคน ที่มาจากพม่า โดยเดินทางมาค้าขายเร่ไปตามบ้าน This article is part of the Cultural Preservation Project entitled Gathering Information of Ethnic Kula in Ubon Ratchathani and Yasothon provinces. It directly focuses on the development of Kula history. The study primarily involves topics as follows: the historical background of Kula, factors contributing their settlement in the study areas, their adjustment in Ubon Ratchathani, and the impacts of their settlement on the research areas. Using the historical approaches, the researcher begins with the process of document gathering, and then focuses on reading the documents analytically and extensively. Moreover, the third stage is collecting the oral history in the field work. Lastly, the researchers synthesize the oral history and documents. As indicated in the research findings, Lao people perceived Ethnic Kula as caravan traders from Burma.